Treatment accuracy of standard linear accelerator-based prostate SBRT: the delivered dose assessment of patients treated within two major clinical trials using an in-house position monitoring system - Arumugam, Sankar; Young, Tony; Jones, Catherine; Pryor, David; Sidhom, Mark (Frontiers in Oncology, 2024)
Background and Purpose: To assess the dosimetric improvements achieved in prostate Stereotactic Body Radiotherapy (SBRT) treatment within the PROMETHEUS and NINJA trials using an in-house real-time position monitoring system, SeedTracker.This study considered a total of 127 prostate SBRT patients treated in the PROMETHEUS (ACTRN12615000223538) and NINJA (ACTRN12618001806257) clinical trials.The SeedTracker position monitoring system was utilized for real-time position monitoring with a 3mm position tolerance. The dose delivered to the Clinical Target Volume (CTV), rectum, and bladder were assessed by incorporating the actual target position during treatment. The dose that would have been delivered without monitoring was also assessed by incorporating the observed position deviations.Results: Treatment with position corrections resulted in a mean (range) CTV D99 difference of -0.3 (-1.0 -0.0) Gy between the planned and delivered dose. Without corrections, this difference would have been -0.6 (-3.7 -0.0) Gy. Not correcting for position deviations resulted in a statistically significant difference between the planned and delivered CTV D99 (p<0.05). The mean (range) dose difference between the planned and delivered D2cc of the rectum and bladder for treatment with position corrections was -0.1 (-3.7 -4.7) Gy and -0.1 (-1.7 -0.5) Gy, respectively. Without corrections, these differences would have been -0.6 (-6.1 -4.7) Gy and -0.2 (-2.5 -0.9) Gy.SeedTracker improved clinical dose volume compliance in prostate SBRT. Without monitoring and corrections, delivered dose would significantly differ from the planned dose.